Expressing Philosophical Discourse In Pencak Silat As A Pillar of Character Education And Strengthening Social Ties In Society - Sarbaitinil, Sarbaitinil; Rudagi, Reindy; Rahmat, Indra; Elfemi, Nilda; Isnaini, Isnaini (ppjbsip, 2023)
The interest in pencak silat is waning, evident in the current generation's preference for kempo, karate, and taekwondo. However, pencak silat holds significant societal value, fostering a heightened sense of concern for others. This study aims to explore and analyze the philosophical discourse of pencak silat as a fundamental element of character education and social cohesion in society. The research methodology adopted is a literature study, involving a thorough search and review of various works on pencak silat, encompassing art, culture, and aesthetics, as well as its role in strengthening social bonds among teachers, students, and their peers. The findings of this study emphasize that pencak silat is a valuable cultural heritage of Indonesia's ancestors, deserving preservation and conservation as it serves as a cornerstone of character education, encompassing nine core values. These character values are deeply ingrained within pencak silat, making it an effective platform for fostering personal growth and moral development. Through pencak silat, social bonds are fortified, leading to enhanced camaraderie and harmonious relationships among different community groups. Two essential aspects that contribute to strengthening social ties in pencak silat are the sense of brotherhood among practitioners and the cultivation of strong spiritual values that resonate within every student engaged in pencak silat training.